Pengaruh Kepemimpinan, Beban Kerja, dan Kemampuan Kerja terhadap Turnover Intention Karyawan pada PT Pendidikan Maritim dan Logistik Indonesia (PMLI) Bogor - Syifa Fauziah; Tini Kartini; Sudarijati Sudarijati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the influence of leadership, workload and work ability on employee turnover intention at PT Pendidikan Maritim Dan Logistik Indonesia (Pmli) Bogor. Before an employee takes a turnover action, it is usually preceded by turnover intention. In this research, the cause of the employee's desire to stop working is thought to be leadership that is not working well, too much workload and a mismatch in abilities and job duties. Sampling of 100 employees was carried out using proportional stratified random sampling. The analytical method used in the research is descriptive and verification methods. Data collection techniques through questionnaires, observation, interviews and literature study. Data analysis uses multiple regression analysis, coefficient of determination analysis, F test and t test. The results of this research show that the variables of leadership, workload and work ability simultaneously have a positive and significant effect on employee turnover intention. Meanwhile, partially leadership and workload have a positive and significant effect on employee turnover intention and work ability has a negative and significant effect on employee turnover intention.